The Deadlocked Debate about the Role of the Jewish Christians at the Birth of Islam - Río Sánchez, Francisco F. del (Religions, 2021)
The thesis concerning the Jewish-Christian origins of Islam has been continuously defended and developed by a good number of authors, even if the proponents of this line of thought have never constituted a school nor followed a unitary or homogeneous discourse. At the other end of the spectrum, many scholars strongly reject the ‘Jewish-Christian connection’ insofar as it introduces a speculative and unnecessary category in the study on the origins of Islam. The matter has aroused irreconcilable stances, studies that remain alien to each other, or simply seem to ignore the status quaestionis. From the traditional perspective, the debate seems to have reached a deadlock, however, and to explain a possible legal, cultural, and religious ‘Judaeo-Christian’ continuum that could be shared by the early Islamic audience, it might be useful to look around the spectrum of mixed beliefs and practices between the Jewish and Christian orthodoxy that can be found at a time very close to the arrival of Islam.